The Experiences of Adolescents in Building Self-Control in Huta III Nagori Manik Maraja, Sidamanik District, Simalungun Regency - sekar asyfa ayuningtias; Jarnawi Jarnawi; Juli Andriyani (Jurnal Kajian dan Pengembangan Umat, 2026)
Adolescence is a period filled with various challenges, during which individuals begin to build their identity and learn to regulate themselves. One of the crucial aspects that adolescents need to possess is the ability to exercise self-control, which includes regulating thoughts, emotions, and behaviors in accordance with the positive values surrounding them. This study aims to examine more deeply adolescents’ experiences in identifying weaknesses in self-control, strategies for building self-control, as well as supporting and inhibiting factors in the development of self-control. This study employed a qualitative approach with a phenomenological study design to obtain a holistic understanding of the participants’ subjective experiences. The participants consisted of six female adolescents aged 15–17 years who were selected through purposive sampling based on the self-control problems they experienced, including verbal aggressiveness, gadget addiction, withdrawal behavior, susceptibility to peer influence, unstable emotions, and high emotional reactivity. Data were collected through in-depth interviews and participatory observation. The data were analyzed using Colaizzi’s thematic analysis technique. The findings revealed three themes. The study showed that the experience of building self-control is a long process influenced by internal factors such as self-awareness and motivation, as well as external factors such as family support and the social environment.